2006
DOI: 10.1021/ma061370w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bulk Viscosity on the Catalytic Chain Transfer Polymerization of CO2-Expanded Butyl Methacrylate and Styrene

Abstract: The catalytic chain transfer polymerization of CO2-expanded butyl methacrylate and styrene is reported. Experimentally determined values of the chain transfer constant for CO2-expanded butyl methacrylate are presented at 50 and 60 °C and in the range of pressure from 0.1 to 6 MPa, using a cobaloxime complex as the chain transfer catalyst. Similar data are reported for CO2-expanded styrene at 50 °C. The chain transfer constants for both expanded monomers are significantly higher than those obtained in the bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…22,23,27 More recently, the controlled polymerisations of MMA, butyl methacrylate and styrene in scCO 2 using CoPhBF as a catalytic CTA have been reported, and was also shown to produce the target low Mwt polymers terminated by the vinylic functionality characteristic of a CCTP reaction. [31][32][33] Hence, this work demonstrated that this control mechanism has the potential to be operated in as a low/zero VOC process. Furthermore, as the catalyst activity was reported to be much higher in scCO 2 than in conventional solvents, this was also concluded to support the proposal that CCTP is diffusion controlled, because the use of scCO 2 is known in increase diffusivity of species such as catalysts within a reaction medium.…”
Section: Introductionmentioning
confidence: 67%
“…22,23,27 More recently, the controlled polymerisations of MMA, butyl methacrylate and styrene in scCO 2 using CoPhBF as a catalytic CTA have been reported, and was also shown to produce the target low Mwt polymers terminated by the vinylic functionality characteristic of a CCTP reaction. [31][32][33] Hence, this work demonstrated that this control mechanism has the potential to be operated in as a low/zero VOC process. Furthermore, as the catalyst activity was reported to be much higher in scCO 2 than in conventional solvents, this was also concluded to support the proposal that CCTP is diffusion controlled, because the use of scCO 2 is known in increase diffusivity of species such as catalysts within a reaction medium.…”
Section: Introductionmentioning
confidence: 67%
“…When a monomer/polymer solution is expanded with compressed CO 2 , the system initially comprises two phases: the CO 2 ‐expanded liquid phase and a CO 2 gas phase. At sufficiently high pressures, the dissolved CO 2 induces a phase separation in the liquid phase at the point known as the homogeneous expansion limit (HEL) 2, 3. This phase separation can create a fine emulsion where the continuous phase comprises CO 2 /monomer and the dispersed phase comprises CO 2 /monomer/polymer.…”
Section: Introductionmentioning
confidence: 99%
“…59 There seems to be only one exception to this rule and that is when supercritical CO 2 (scCO 2 ) is used as the solvent. 62,64,112 In this very low-viscosity medium the measured chain transfer constants are much higher than in bulk or common solvents and with only small effects on k p this means that k tr is much higher.…”
Section: Mechanistic Aspects Of Catalytic Chain Transfermentioning
confidence: 81%